Transitioning and re-membering of academics in times of upheaval. Issue 2 (4th March 2021) - Wilson, Anat; Goff, Wendy; Pale, Maryanne; Turner, Kristina
ABSTRACT: The higher education landscape has been amidst change over recent years. At the time of writing this paper, the pandemic outbreak has had a substantial impact on the higher education sector. This was our last year as early career researchers, but the prospect of promotion was replaced with managing unpredicted short-term job insecurity. In writing this article, we engage with collaborative diffractive autobiographical writing, re-membering, re-connecting and re-experiencing our autobiographical accounts, written at the beginning of our transition into academia. Through diffractive analysis, we shifted from positivistic approaches that assume a rigid separation between observer and the observed, to engage in an ongoing (re)pattering and (re)(con)figuring of our identities during this transition. In an intentional disruption of binary, we engage in writing as an event of interaction with texts, allowing ourselves to be affected by and experience these propositions in their mutual entanglements.